Pengembangan Media Pembelajaran Interaktif berbasis Digital untuk Meningkatkan Minat Belajar Siswa pada Mata Pelajaran Bahasa Indonesia Kelas IV di SD Inpres Bertingkat Oebobo II, Kota Kupang - Natalia Messakh; Markus Sampe; Rista Apriliya Devi (Lembaga Yasin AlSys, 2025)
This study was motivated by the low learning interest among fourth-grade students in Indonesian language classes at SD Inpres Bertingkat Oebobo II, Kota Kupang. The objective of the research was to develop a valid and practical digital-based interactive learning media and to evaluate its effectiveness in enhancing students’ learning interest. The study employed a Research and Development (R&D) method using the ADDIE development model, which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. The developed product was an interactive PowerPoint learning media, which was then validated and assessed for feasibility. The research subjects were fourth-grade students, and data were collected through observation, interviews, expert validation, pre-test and post-test assessments, as well as student response and interest questionnaires. Validation results from media and content experts showed a validity percentage of 92%, categorized as